(untitled) (Research Data Journal for the Humanities and Social Sciences, 2024)
Studying Russian society is challenging, especially during the period of the Russian military invasion. However, it takes on special significance during a period of economic and social transformation. Studying the career and educational trajectories of Russians in the context of East Studies offers a multifaceted perspective on the state of the job market and education sector and gives an understanding of the current situation of the country’s economy and social structure. The lack of data with a high level of granularity is critical, especially for studying people with a focus on their career and educational trajectories. In this article, the authors respond to this request and present two datasets that can be useful for studying spatial and temporal patterns associated with people’s life trajectories in the context of work and education. The authors utilised open data on cv s created or updated by employment portal users over the period 2015–2023 from the Federal Service for Labor and Employment (Rostrud) and prepared two cleaned datasets covering 83 regions of Russia. Dataset 1 is on the educational and career trajectories (N = 6,221,439) and Dataset 2 is on the activity of unemployed and job-seeking candidates (N = 7,662,089).